Pengaruh Digital Marketing, Brand Awareness, dan Endorsement Influencer terhadap Penjualan Produk Generos di PT Quantum King Sulaiman - Fajriyah, Darari; Vindiana, Afina Putri; Rosyidta P.O, Annuridya; Tampubolon, Edward S. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The rapid growth of digital technology has transformed marketing practices, requiring companies to adopt innovative strategies to remain competitive. PT Quantum King Sulaiman, the producer of Generos herbal products, faces intense market competition and therefore needs to optimize digital marketing, strengthen brand awareness, and leverage influencer endorsement to increase sales. This study aims to analyze the influence of these three factors on Generos sales through a structured literature review of national and international journals published between 2020-2025. The findings show that digital marketing effectively expands consumer reach and engagement at relatively low cost, brand awareness enhances consumer trust and loyalty by creating a positive brand image, and influencer endorsement significantly shapes purchase decisions through credibility and emotional connection. The synthesis also highlights that the combined implementation of these strategies has a stronger impact than using them individually. This study contributes by emphasizing the relevance of integrated digital marketing strategies in the herbal product sector, which has received limited academic attention. However, as a literature-based study, the findings need to be validated through empirical research involving consumer data to capture real behavioral patterns.